A Sociolinguistic Approach to the Problem of Anglicisms in Armenian - Galstyan, Anahit; Galstyan, Hayk (Armenian Folia Anglistika, 2011)
A sociolinguistic analysis has been conducted among Armenians living in the USA and the Republic of Armenia with an aim to find out the attitude of the Armenian-speaking community to the use of English words and expressions in Armenian written and oral speeches. Two methods have been applied – an interview and questionnaires. 320 Armenians living in the USA and 564 Armenian citizens have participated in the experiment. The findings obtained demonstrate the following: Armenians who were born in a foreign country are more inclined to struggle to keep the language unaffected by foreign borrowings than Armenian citizens and the Armenians who have emigrated to the USA. The latter are more concerned about learning English than preserving the Armenian language and culture pure.